Grassroots Post-modernism : Remaking the Soil of Cultures. - Esteva, Gustavo (Critique, influence, change., 2014)
In this classic text Gustavo Esteva and Madhu Suri Prakash examine the post-modern epic unfolding at the grassroots and the mass movement away from the monoculture of a single global society.